Towards Underwater Macroplastic Monitoring Using Echo Sounding - Broere, Sophie; van Emmerik, Tim; González-Fernández, Daniel; Luxemburg, Willem; de Schipper, Matthieu; Cózar, Andrés; van de Giesen, Nick (Frontiers in Earth Science, 2021)
Plastics originating from land are mainly transported to the oceans by rivers. The total plastic transport from land to seas remains uncertain because of difficulties in measuring and the lack of standard observation techniques. A large focus in observations is on plastics floating on the water surface. However, an increasing number of observations suggest that large quantities of plastics are transported in suspension, below the water surface. Available underwater plastic monitoring methods use nets or fish traps that need to be deployed below the surface and are labour-intensive. In this research, we explore the use of echo sounding as an innovative low-cost method to quantify and identify suspended macroplastics. Experiments under controlled and natural conditions using a low-cost off-the-shelf echo sounding device show that plastic items can be detected and identified up to 7 m below the river surface. Eight different debris items (metal can, cup, bottles, food wrappers, food container) were characterized based on their reflection signature. Reflectance from plastic items diverged significantly from organic material and non-plastic anthropogenic debris. During a multi-day trial field expedition in the Guadalete river, Spain, half of the observed plastics items were found below the surface. As most plastic monitoring and removal strategies focus on the upper layer, a substantial share of the total plastic transport may be neglected. With this paper we (1) demonstrate that echo sounding is a promising tool for underwater plastic monitoring, and (2) emphasize the importance of an improved understanding of the existing plastic loads below the surface.